Heterogeneous Porous Synergistic Photocatalysts for Organic Transformations - Zhu, Yuan‐Yuan; He, Yuan‐Yuan; Li, Yan‐Xiang; Liu, Chun‐Hua; Lin, Wenbin (Chemistry : a European journal, 2024)
Recent interest has surged in using heterogeneous carriers to boost synergistic photocatalysis for organic transformations. Heterogeneous catalysts not only facilitate synergistic enhancement of distinct catalytic centers compared to their homogeneous counterparts, but also allow for the easy recovery and reuse of catalysts. This mini‐review summarizes recent advancements in developing heterogeneous carriers, including metal–organic frameworks, covalent–organic frameworks, porous organic polymers, and others, for synergistic catalytic reactions. The advantages of porous materials in heterogeneous catalysis originate from their ability to provide a high surface area, facilitate enhanced mass transport, offer a tunable chemical structure, ensure the stability of active species, and enable easy recovery and reuse of catalysts. Both photosensitizers and catalysts can be intricately incorporated into suitable porous carriers to create heterogeneous dual photocatalysts for organic transformations. Notably, experimental evidence from reported cases has shown that the catalytic efficacy of heterogeneous catalysts often surpasses that of their homogeneous analogues. This enhanced performance is attributed to the proximity and confinement effects provided by the porous nature of the carriers. It is expected that porous carriers will provide a versatile platform for integrating diverse catalysts, thus exhibiting superior performance across a range of organic transformations and appealing prospect for industrial applications. Porous materials including metal–organic frameworks (MOFs), covalent–organic frameworks (COFs), and porous organic polymers (POPs) have recently been established as an ideal platform to enhance synergistic photocatalysis for organic transformations. Benefitting from the designability of these molecular materials, both photosensitizers and catalysts can be intricately incorporated into the porous carriers, leading to greatly enhanced performance over their homogeneous counterparts.